Relações climáticas com o crescimento e desenvolvimento do xilema do tronco de Hymenaea stigonocarpa Mart. ex Hayne em ecótono Cerrado-Pantanal - Roquette, José Guilherme (2022)
The climate in tropical regions allows and governs the existence of the greatest biodiversity on Earth. In recent decades, evidence has pointed to changes in climatic conditions in these regions, whose main cause is attributed to the emission of greenhouse gases by human activities, causing an increase in the average global temperature. Changes in the hydrological regime in the ecotone region between Cerrado and Pantanal have been observed in recent years, with an increase in average temperature and the occurrence of severe droughts for the next decades in the region, which could impact existing ecosystems and the rich regional biodiversity. In this context, trees are essential for a better understanding of the changes that are taking place, as they record in their tissues throughout their growth, notably in the xylem, information about the climate of the place where they grow, with annual resolution. Chapter 1 addresses the issue of climate change, its impacts on trees (with emphasis on tropical species) and the foundations and methods for dendroclimatological studies. Although this science has expanded in the tropics in recent years, many challenges still need to be faced in order to increase knowledge about the species, the past climate and the changes that may occur in these regions according to predicted climate change scenarios. Thus, the objective of Chapter 2 was to evaluate the climatic relationships with the growth of Hymenaea stignocarpa Mart. ex Hayne, in order to identify its potential for dendrochronological studies and better understand how the species' growth responds to climatic variations. Xylem samples were collected at breast height from 67 trees to construct a dendrochronological series from cross-dating with the width of the growth rings, and the correlations with indices of large-scale atmospheric circulations from the Pacific and Atlantic oceans were analyzed, as well as meteorological variables related to water availability, air temperature and solar radiation. Positive and significant correlations were observed with the Pacific Decadal Oscillation Index during the growth period. Maximum and average temperatures negatively influenced growth at the beginning, while precipitation positively influenced growth at the beginning and end of this period. At the end of the rainy season, the correlations between growth with air temperatures and rainfall reversed, suggesting that poorly drained soil conditions affect growth when there is water saturation, and this effect can be minimized with increased insolation and consequent evaporation of water. Finally, Chapter 3 aimed to evaluate the potential of different variables in the xylem growth rings of the trunk of Hymenaea stgnocarpa Mart. ex Hayne in the Cerrado-Pantanal ecotone, from the comparison with the chronological series dated from the width of the growth rings. Variables related to vessels, fibers and parenchyma were measured, in addition to the density and values of stable isotopes of 13C and 18O. It was observed that other variables of the growth rings have stronger correlations with meteorological variables, atmospheric circulation and drought indices, when compared to the width of the growth rings. The variables of the anatomical elements presented significant correlations with measures of accumulated precipitation, total insolation, air temperature, and atmospheric circulation index of the Central-South Atlantic Ocean, before and during the growth, depending on the climatic variable. The 13C isotopes showed positive correlations mainly with total insolation and rainfall during growth, and negative correlations with the atmospheric circulation index in the North Atlantic Ocean before growth. The 18O isotopes and the density showed significant correlations with droughts, in addition to rainfall and air temperature, respectively, constituting promising proxies for studies of extreme climatic events in the region.